A retrospective analysis of bone tumors and tumor like lesions: a hospital based study of 76 cases - Deka, Manoj Kumar; Talukdar, Anuradha (International Journal of Research in Medical Sciences, 2017)
Background: Globally Bone tumors constitute 0.5% of the total World Cancer Incidence. In addition to benign and malignant bone tumors there are a number of nonneoplastic lesions that present in a manner similar to neoplastic conditions. Relevant demographic features such as age, sex and skeletal site are important to come to a conclusive diagnosis. The present study aims to show the prevalence and demography of bone tumors and tumor like lesions. Methods: A total of 76 cases of Bone Tumors and Tumor like Lesions were studied. They were reviewed and analyzed for age, gender, site of tumor and histologic types. Classification was done according to WHO histologic Classification of Bone Tumors. Results: There were 49 cases of primary bone tumors and tumor Like lesions with a median age of 22 years and 27 cases of metastatic bone tumors with a median age of 56 years. Males are more commonly affected. Osteosarcomas and Chondrosarcomas are the most common primary malignant Bone Tumors. Conclusions: Metastatic bone tumors constitute the highest number of bone tumors occurring at an older age group. Maximum numbers of bone tumors are found in the age range 11-20 years and all are primary bone tumor and tumor like lesions.